ANALISIS GEOWISATA BERDASARKAN GEOSITE DAERAH TEBING TINGGI KABUPATEN EMPAT LAWANG SUMATERA SELATAN - Muhammad Pasma Ajiansyah; Endang Wiwik Dyah Hastuti (Fakultas Pertanian, 2022)
Empat Lawang Regency is one of the regencies in South Sumatra which is known for its pretty good geotourism potential. The location of Empat Lawang Regency which is in the South Sumatra basin, with the influence of tectonic control and sedimentation which tends to be diverse and dominant, makes the research location contain forms and landscapes with a variety of beauty and uniqueness, one of which is karst and waterfalls. Thus, research conducted with the aim of knowing the potential of geotourism in depth is very interesting to do. In more detail, this research was carried out in several stages, namely primary and secondary data collection, processing based on Kubalíková's (2013) quantitative value consisting of intrinsic and scientific value, educational value, economic value, conservation value, and additional value, stages of studio work , to the last stage in the form of report preparation. Based on the results of observations that have been made, there are 8 locations that have the potential as geosite areas. However, after an analysis of Kubalíková's (2013) assessment, it turned out that only 5 sites contained an assessment percentage of more than 50% or could be said to be priority sites for development into geotourism areas. These priority sites are contained in a geotrack map consisting of 2 travel destination lines. Geotrack 1 contains the Sanghe Waterfall Puyang Berang Sane Statue - Serunting Sakti River. Meanwhile, the Geotrack 2 route contains the Black Pool and Mekarjaya Cave.